Reverse Osmosis Polyamide Membrane for the Removal of Blue and Yellow Dye from Waste Water - Mustafa H. AL – Nakib, Nada (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
The present work aims to study the removal of dyes from wastewater by reverse osmosis process. Two dyes were used direct blue 6, and direct yellow. Experiments were performed with feed concentration (75 – 450 ppm), operation temperature (30 – 50 oC) and time (0.2 – 2.0 hr). The membrane used is thin film composite membrane (TFC). It was found that modal permeate concentration decreases with increasing feed concentration and time operating, while permeate concentration increases with increasing feed temperature. Also it was found that product rate increase with increasing temperature, but it decrease with increasing feed concentration and time. The concentration of reject solution showed an increase with increasing feed concentration of dyes and feed temperature, while decreases with increasing time operating of reverse osmosis unit. The maximum rejection for direct blue 6 and direct yellow are 98.89% and 98.30% respectively. The maximum recovery percentage for direct blue 6 and direct yellow are 17.84% and 18.20% respectively. The maximum concentration factor of direct blue 6 is 1.227 and for direct yellow is 1.272.